2017
DOI: 10.1002/da.22613
|View full text |Cite
|
Sign up to set email alerts
|

PTSD and cognitive symptoms relate to inhibition-related prefrontal activation and functional connectivity

Abstract: Background Posttraumatic stress disorder (PTSD) is associated with reduced executive functioning and verbal memory performance, as well as abnormal task-specific activity in prefrontal (PFC) and anterior cingulate cortices (ACC). The current study examined how PTSD symptoms and neuropsychological performance in combat veterans relates to 1) medial PFC and ACC activity during cognitive inhibition, and 2) task-independent PFC functional connectivity. Methods Thirty-nine male combat veterans with varying levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 53 publications
4
49
0
4
Order By: Relevance
“…The differences in cognitive function align with the fronto-limbic hypothesis of PTSD, which postulates that PTSD symptoms, including impaired cognition, may result from alterations in the structure and function of brain regions comprising this circuit (e.g., prefrontal cortex, hippocampus, amygdala;Clausen et al, 2017;Polak, Witteveen, Reitsma, & Olff, 2012;Scott et al, 2015;Wrocklage et al, 2016).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…The differences in cognitive function align with the fronto-limbic hypothesis of PTSD, which postulates that PTSD symptoms, including impaired cognition, may result from alterations in the structure and function of brain regions comprising this circuit (e.g., prefrontal cortex, hippocampus, amygdala;Clausen et al, 2017;Polak, Witteveen, Reitsma, & Olff, 2012;Scott et al, 2015;Wrocklage et al, 2016).…”
supporting
confidence: 64%
“…The differences in cognitive function align with the fronto‐limbic hypothesis of PTSD, which postulates that PTSD symptoms, including impaired cognition, may result from alterations in the structure and function of brain regions comprising this circuit (e.g., prefrontal cortex, hippocampus, amygdala; Clausen et al, ; Polak, Witteveen, Reitsma, & Olff, ; Scott et al, ; Wrocklage et al, ). Further, the reduced hippocampal volume is a relatively consistent finding in individuals with PTSD (Karl et al, ; Kitayama, Vaccarino, Kutner, Weiss, & Bremner, ; Woon, Sood, & Hedges, ).…”
Section: Introductionsupporting
confidence: 55%
“…In general, it is found that amygdala response is exaggerated in PTSD subjects, and is more pronounced when PTSD symptoms are more severe (Brunetti et al, ; Dickie, Brunet, Akerib, & Armony, ; Shin et al, ; Zhong et al, ). Modulation/extinction of the fear response is postulated to involve an inhibitory role of medial prefrontal structures, particularly the ACC, over the amygdala (Clausen et al, ; Shin et al, ; Stevens et al, ). In PTSD diagnosed subjects, correlational analyses from the current study identified associations between FA/RD/AD/MD values and PTSD symptoms (as measured by CAPS subscores) in WM tracts connecting the amygdala and ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it could reflect a compensatory mechanism for maintaining focus during sustained attention tasks that stops working with more difficult inhibition tasks 80 . Another interpretation is that this pattern of activity reflects a decreased ability to regulate midline cortical self-referential processing activity during attentional tasks 84 . It is yet to be determined how these changes in PFC engagement might also alter the hippocampal-related declarative memory processes discussed above.…”
Section: Altered Cognition and Moodmentioning
confidence: 99%